Association between income and perinatal mortality in the netherlands across gestational age - Vidiella-Martin, J; Been, JV; Van Doorslaer, E; García-Gómez, P; Van Ourti, T (American Medical Association, 2021)
Importance The association between household income and perinatal health outcomes has been understudied. Examining disparities in perinatal mortality within strata of gestational age and before and after adjusting for birth weight centile can reveal how the income gradient is associated with gestational age, birth weight, and perinatal mortality.